Venezuela y Postales de Leningrado: guerrilleros tras un futuro pasado (Revista de Crítica Literaria Latinoamericana, 2023)
Postcards from Leningrad (2007) by Venezuelan director Mariana Rondón questions how the guerrilla struggle in Venezuela in the 1960s goes through the forms of technical reproduction in the formulation of cultural discourses, social temporalities and regimes of historicity that, together, interrogate pasts, presents and futures. Through the analysis of the film, this article interrogates the postulation of identities at the crossroads of time, at the crossroads of discourses, behind a sense and a form of history and culture—of the Revolution, of Modernity— intertwined by realities and fictions, by triumphs and failures.
Keywords: Venezuela; Bolivarian Revolution; guerrillas; Latin America; Postales de Leningrado